Encyclopedia of international relations and global politics - Griffiths, Martin (Routledge, 2005)
the study of international relations has changed rapidly in recent years. One reason is the pace of major political and economics change - the end of the Cold War and the fall of communism; the resurgence of nationalism;terrorism and other forms of fundamentalism; and of course, globalization.